Determine the most important factors affecting liver cancer i n Iraq for the year 2017 (Journal of the College of Basic Education, 2019)
The logistic regression is one of the most important elements of linear modeling. It is one of the most statistical methods used in the analysis of classified data and does not assume any conditions for the distribution of independent variables. Logistic regression is used to predict the probability of a particular event in many different fields, including medical, economic, social sciences and other fields that require predicting the tendency of people to make decisions about current study. This type of regression is flexible, giving a clear explanation for the relationship between the dependent variable and the explanatory variables.The study examined the use of logistic regression to determine the most important factors and variables affecting patients with liver cancer in Iraq for the year 2017, by analyzing the relationship between variables and access to variables that affect of this type of cancer. One of the most important conclusions reached by the researcher is to identify the most important factors affecting liver cancer and the cause of the disease in order to avoid the incidence of such a type of disease.